1990
DOI: 10.1542/peds.85.5.715
|View full text |Cite
|
Sign up to set email alerts
|

Meconium Aspiration Syndrome: Have We Made a Difference?

Abstract: Meconium aspiration syndrome (MAS) and its associated complications are reviewed from the period before the routine use of intubation and suctioning to the present (1973 through 1987). Of the 176 790 neonates born during this period, the amniotic fluid was stained in 21 472 (12.15%). Subsequently, MAS developed in 1162 (5.41%) of the meconium-stained neonates. Male neonates were more prone to the disorder than female neonates (P = .022). There were no racial predilections for MAS. The incidence of MAS signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
2
5

Year Published

1992
1992
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(28 citation statements)
references
References 0 publications
1
20
2
5
Order By: Relevance
“…The rate of MSAF deliveries in our study was 3.8% compared to 7-22% from previously reported studies in term pregnancies [ 1 , 2 ]. This may be in part due to earlier inductions and deliveries and a low threshold for cesarean sections.…”
Section: Discussioncontrasting
confidence: 67%
“…The rate of MSAF deliveries in our study was 3.8% compared to 7-22% from previously reported studies in term pregnancies [ 1 , 2 ]. This may be in part due to earlier inductions and deliveries and a low threshold for cesarean sections.…”
Section: Discussioncontrasting
confidence: 67%
“…One third of all infants with MAS require mechanical ventilation. 33 Fox and colleagues 34 as well as Truog et a135 found endotracheally applied continuous positive-end expiratory pressure /PEEP} to improve oxygenation in babies 3~ and lambs 35 with MAS. By contrast, some investigators 36 have found that air trapping and increased functional residual capacity (factors that increase the risk of air leaks) may be exacerbated by the application of PEEP.…”
Section: Neonatal Management All Infants With Masmentioning
confidence: 98%
“…Additionally, boys tend to respond less favorably to therapeutic efforts intended to improve pulmonary function antenatally, with administration of steroids (Ballard et al, 1980; Papageorgiou, Colle, Farri-Kostopoulos, & Gelfand, 1981), or postnatally, with administration of surfactant (Arnold, Adams, Torres, & Sidebottom, 1996; Corchia et al, 1997). In comparison with their female counterparts, boys have higher rates of cerebral palsy (Sizun et al, 1998; Spinillo et al, 1997), as well as ante-, peri-, and postnatal complications (for an overview, see Raz et al, 1994), such as preeclampsia (Brothwood, Wolke, Gamsu, Benson, & Cooper, 1986), certain types of intrauterine growth retardation (Spinillo et al, 1994), prematurity (Khoury et al, 1985), abruptio placenta and placenta previa (James, 1995), neonatal infections (Fanaroff et al, 1998), anemia, apnea and hypocalcemia (Brothwood et al, 1986), hypoglycemia (Corchia et al, 1997), intracranial hemorrhage (Amato, Howald, & von Muralt, 1987; Shankaran, Bauer, Bain, Wright, & Zachary, 1996), and meconium aspiration (Wiswell, Tuggle, & Turner, 1990). Boys are also at greater risk for developing neonatal respiratory distress than are girls of the same gestational age (Brothwood et al, 1986; Catlin et al, 1990; Torday, Nielson, Fencl, & Avery, 1981), and their odds of developing chronic lung disorders during the neonatal period are increased (Korhonen, Tammela, Koivisto, Laippala, & Ikonen, 1999; Todd, Jana, & John, 1997).…”
mentioning
confidence: 99%